Effective communication for managers : getting your message across - Simons, Chris; Naylor-Stables, Belinda (London : Cassell, 1997)
This book is divided into three parts: How we communicate the message through our behaviour; How we communicate the message through the written word; and How we communicate the message through information technology.
Keywords: Business; Management; Communication; Communication in management; Business communication